Regulatory and Educational Initiatives to Prevent Food Choking Injuries in Children: An Overview of the Current Approaches - Lorenzoni, Giulia; Hochdorn, Alexander; Beltrame Vriz, Giulia; Francavilla, Andrea; Valentini, Romina; Baldas, Solidea; Cuestas, Giselle; Rodriguez, Hugo; Gulati, Achal; van As, A. B. Sebastian; Gregori, Dario (Frontiers in Public Health, 2022)
Choking injuries are one of the major causes of death among children ages 0–3, and most of these injuries are related to food. This work provides an overview of the current recommendations for food choking prevention and educational targets as a basis for developing a unified common set of knowledge for primary prevention policies development. Guidelines published by professional membership organizations and national governments in the English language were considered. All of these guidelines provide lists of hazardous food items and recommendations for food preparation to minimize choking hazard. Together with recommendations for food preparation, also recommendations aimed at stakeholders (food manufacturers, health care providers, and public authorities) are provided, underlining that this severe public health problem should be further addressed by adopting integrated public health interventions. Our overview stressed the importance of developing educational and primary prevention policies to sensitize adult supervisors and to regulate dangerous food products in the market.